Assessment of material and technical resources of crop production technologies - V. M. Beylis (Сельскохозяйственные машины и технологии, 2017)
The author explains the general principles of influence of the material and technical resources (MTR) on performance and efficiency of the main technological operations in crop production. Various technologies from the point of view of MTR expenses were estimated. The general tendencies in development of crop production technologies were revealed. The distribution of costs of materials and equipment to perform a variety of agricultural activities was determined. Cost indicators should be a guide in the search of innovative technological processes and working elements of agricultural machins. The greatest values of expenses of work, fuel, metal, and also, money where found. The concepts allowing to provide costs production reduction were formulated. To achieve the maximum productivity with the minimum expenses, the perspective calculations shoul be based on «progressive» agrotechnologies. When determining progressive agrotechnology it is necessary on reasonable grounds to approach indicators of crop productivity in various agrozones and regions of the country. For an assessment of efficiency of MTR by crop production and ensuring decrease in resource intensity of agricultural products by search and use of essentially new technologies for energy saving when performing agricultural operations, an integrated percentage indicator of comparison of progressive technologies with the applied ones was developed. MTR at application of new progressive crop production technologies by integrated percentage index were estimated. This indicator can be used for definition of efficiency of MTR. Application of the offered technique will promote an effective assessment of MTR, decrease in resource intensity by search and developments of essentially new technologies of performance of operations in crop production.